Fault prediction for power transformer using optical spectrum of transformer oil and data mining analysis - Fauzi N.A.; Ali N.H.N.; Ker P.J.; Thiviyanathan V.A.; Leong Y.S.; Sabry A.H.; Jamaludin M.D.Z.B.; Lo C.K.; Mun L.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost effectiveness; Data mining; Electric discharges; Fault detection; Forecasting; Oil tanks; Optical correlation; Optical materials; Power transformers; Spectrum analysis; Voltage control; Data analytic tools; Dissolved gas analysis; Electrical discharges; On- load tap changers; Optical characteristics; Optical spectroscopy; Optical spectroscopy techniques; Periodic preventive maintenance; Oil filled transformers